(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
This study aims at identifying the causes and roots of international financial crises which have become frequent and rapid. This study will analyze the concept of financial crises by identifying this concept, examining the stages which reflect the historical development of financial crises, shedding light, with great emphasis, on the current financial crises, In regard to its stages, roots, causes and impacts. This study will seek to examine the several unsolved questions between financial economy and real economy, either resulting from latent contradictions in international economy or from structural defects of International Financial System. This study tries to answer several questions, the most important of which are the following: what is meant by financial crises? What are the causes and roots of financial crises? What are the consequences of such crises on the long and short terms? What are the possible solutions for these crises?. In this study, the researcher will follow the inductive approach, namely, getting the general rules from particular facts, because of the redundant amount of details, data and indicators related to the issue of financial crises. The researcher will emphasize the impact on the economies of a sample of countries which are considered to be the richest and most efficient in different regions in the world, in a away that may give a general impression on the whole International Economy, this study will be based, in its analysis, on the descriptive analytical approach, by referring to the series of successive financial crises and different opinions about the causes and roots of the crises, attitudes and measures taken by the countries negatively affected by such crises.